Learning experience and barriers throughout open distance learning mode: A case study of UiTM Pahang students / Noor Hasimah M Yacob …[et al.] - M Yacob, Noor Hasimah; Mohammad Fadzillah, Nur Syazwani; Wan Abdul Rahman, Nor Hawani; Mustafa, Lily Mazlifa; Jamaluddin, Sabariah; Mat Bahari, Anis Barieyah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Due to the pandemic of Covid19, UiTM moved all classes to online and distance learning (ODL) mode effective from April 13, 2020 for all its campuses. This sudden change made all the lecturers and students felt difficult and unsure of being able to continue the teaching and learning process throughout ODL mode. However, the academic session must be continued to ensure that the students still can learn, and they can graduate on time. Therefore, this paper aims to study the learning experience of the students and barriers faced throughout the ODL mode. In achieving the objectives of the study, the data were gathered from a set of questionnaires distributed to 723 students in UiTM Pahang, Jengka Branch. The study found that most of the students have a good learning experience dealing with their lecturers during the ODL. However, they have faced several barriers that may lead to dissatisfaction with online learning such as time management, stress and tired, lack of family support, difficulties of students to understand the lesson taught, or materials provided by the lecturers. Only a few of them having a problem with internet and device performance, in term s of technology skills, majority of them were not experts in using Learning Management System (LMS). The result of the study might be used by respective authorities to improve the guidelines regarding the ODL process in the future. Further study should be conducted to see the impact of online learning barriers to their academic performance.